2014
DOI: 10.1371/journal.pone.0104438
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor Activation Reorganizes Neuronal Ensembles during Hippocampal Sharp Waves In Vitro

Abstract: Hippocampal sharp wave (SW)/ripple complexes are thought to contribute to memory consolidation. Previous studies suggest that behavioral rewards facilitate SW occurrence in vivo. However, little is known about the precise mechanism underlying this enhancement. Here, we examined the effect of dopaminergic neuromodulation on spontaneously occurring SWs in acute hippocampal slices. Local field potentials were recorded from the CA1 region. A brief (1 min) treatment with dopamine led to a persistent increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 59 publications
3
28
0
Order By: Relevance
“…In a direct confirmation of this prediction, it was recently reported that optogenetic activation of dopaminergic inputs to the hippocampus enhanced the likelihood of ripple-based pairwise reactivation reflecting a recently explored environment (McNamara et al, 2014). The underlying mechanisms through which neuromodulatory input can impact the rate and content of replay remain unclear (Miyawaki et al, 2014;Rosen et al, 2015).…”
Section: Reward Influences the Content Of Replaymentioning
confidence: 93%
“…In a direct confirmation of this prediction, it was recently reported that optogenetic activation of dopaminergic inputs to the hippocampus enhanced the likelihood of ripple-based pairwise reactivation reflecting a recently explored environment (McNamara et al, 2014). The underlying mechanisms through which neuromodulatory input can impact the rate and content of replay remain unclear (Miyawaki et al, 2014;Rosen et al, 2015).…”
Section: Reward Influences the Content Of Replaymentioning
confidence: 93%
“…Cellular participation during SWRs was assessed by constructing a simplified 290 event matrix with SWRs in one dimension, and cells in the other, with a zero or one if the cell reached 291 threshold during the SWR. For fields with five or more active cells, the ensemble diversity was assessed 292 by calculating the pairwise Jaccard Similarity index between SWR events, ranging from a value of zero 293 if two SWR events had no cells in common, to a value of one if all cellular participants were identical, 294 modeled after the analysis of (Miyawaki et al, 2014). The cell-cell pairwise index was also calculated, 295 ranging from zero if two cells never participated in the same SWR events, to one if they participated in 296 precisely the same SWRs.…”
Section: Calcium Transient Detection and Swr Coincidence Analysis 264mentioning
confidence: 99%
“…Dopamine exerts a multifaceted role in learning (Hollerman and Schultz, 1998), network connectivity (Eytan et al, 2004), and neuronal synchronization (Puig et al, 2014), including a stabilizing influence on cellular activity within neural ensembles (O'Donnell, 2003;Puig and Miller, 2012b;Miyawaki et al, 2014). Dopamine's role in drug reward processing appears to facilitate the encoding of reward prediction, imprinting incentive value to reinforcers (energizing approach behavior) and facilitating learning of reward associations (conditioning) through its modulation of subcortical (including the nucleus accumbens) and cortical brain regions (Di Chiara, 1999;Schultz, 1999;Waelti et al, 2001;Schultz, 2002;Redish, 2004;Steinberg et al, 2013).…”
Section: The Influence Of Dopaminementioning
confidence: 99%
“…This PL-PFC to accumbens core pathway is recruited in a dopamine-dependent manner to drive drug seeking in response to cues (McGlinchey et al, 2016). Dopamine signaling can induce cFos expression (Zhang et al, 2006) and promote the formation and maintenance of activity within cellular neural ensembles (O'Donnell, 2003;Puig and Miller, 2012a;Miyawaki et al, 2014). However, the cellular adaptations that occur within these activated ensembles in the PL-PFC remain unclear.…”
Section: Introductionmentioning
confidence: 99%